Rethinking Translingualism in College Composition Classrooms: A Digital Ethnographic Study of Multilingual Students' Written Communication Across Contexts. (January 2023) - Zhang-Wu, Qianqian
It is important to understand multilingual students' lived experiences and sense-making in their everyday written communication before rethinking the implementation of translingual writing in college composition classrooms. Unpacking multilinguals' written communication across social and academic contexts, this exploratory qualitative study integrates digital ethnographic and interview methods to examine the first-semester communication experiences of 10 undergraduate students. The findings indicate that while participants engaged in translingual written communication as part of their lived experiences in social contexts, they were reluctant to draw upon their home language in academic settings. Based on the findings, I discuss the pedagogical implications of supporting multilingual students in college composition classrooms. I argue that instructors must reposition themselves as co-learners together with their multilingual students to enact a translingual stance in academic settings and reimagine meaningful written communication beyond English-only. This study sheds light on rethinking the pedagogical practices around implementing translingualism in college composition.